2017
DOI: 10.1093/ntr/ntx195
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Product Innovation: Smokers’ Perceptions of Capsule Cigarettes

Abstract: Introduction: Since being brought to market in 2007, cigarettes with capsules in the filter that can be burst to change the flavour have had remarkable global success, highlighting the importance of product innovation for tobacco companies. Very few studies have explored how these products are perceived by smokers however. This paper sought to address this gap by exploring smokers' awareness of cigarettes with one or two flavour-changing capsules in the filter and the appeal of these products. Methods: Twenty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 12 publications
10
61
0
Order By: Relevance
“…At the time of the study, the only bevelled-edged plain packs in the UK were for Pall Mall, which would likely be a more recognisable brand in Turkey than any of the brands used for the straight-edged packs. While brand name was not mentioned within any groups as a factor relating to the greater appeal of the bevelled-edged packs, it is possible that the name, or the fact that all the Pall Mall variants contained flavour-changing capsules, which have been found to appeal to younger people,20 influenced participants' responses. As there are no brands on the UK market that use both straight-edged and bevelled-edged packs, even after the full implementation of plain packaging, to control for brand name future research would need to use mocked-up packs or images.…”
Section: Discussionmentioning
confidence: 99%
“…At the time of the study, the only bevelled-edged plain packs in the UK were for Pall Mall, which would likely be a more recognisable brand in Turkey than any of the brands used for the straight-edged packs. While brand name was not mentioned within any groups as a factor relating to the greater appeal of the bevelled-edged packs, it is possible that the name, or the fact that all the Pall Mall variants contained flavour-changing capsules, which have been found to appeal to younger people,20 influenced participants' responses. As there are no brands on the UK market that use both straight-edged and bevelled-edged packs, even after the full implementation of plain packaging, to control for brand name future research would need to use mocked-up packs or images.…”
Section: Discussionmentioning
confidence: 99%
“…19 Taste, choice of flavours, enjoyment from clicking the capsule, stylishness, and lower perceived harm appear key reasons for using capsule cigarettes. 11,[17][18][19][20][21] Other studies have found that capsule cigarettes are viewed favourably among non-smokers and thought to encourage experimentation, and are perceived as a "cool invention" that is fun and appealing for adolescents and newer smokers. 20,22,23 Regulators have been slow to respond to the threat of capsule cigarettes.…”
Section: Flavour Capsule Cigarettes Continue To Experience Strong Glomentioning
confidence: 99%
“…11,[17][18][19][20][21] Other studies have found that capsule cigarettes are viewed favourably among non-smokers and thought to encourage experimentation, and are perceived as a "cool invention" that is fun and appealing for adolescents and newer smokers. 20,22,23 Regulators have been slow to respond to the threat of capsule cigarettes. As of 2018 only Canada, Ethiopia, Senegal, and Uganda had banned flavoured tobacco products, although they will be banned in Brazil by March 2020 and, as a result of the Tobacco Products Directive, across much of Europe by May 2020; 24 these bans do not cover nonflavour capsules, such as the cigarettes with water capsules (e.g.…”
Section: Flavour Capsule Cigarettes Continue To Experience Strong Glomentioning
confidence: 99%
See 1 more Smart Citation
“…Given that capsule cigarettes appeal to youth20 21 and are perceived as more stylish and less harmful than regular cigarettes,22 capsule heat-sticks may also appeal to youth. Like capsule cigarettes, capsule heat-sticks contain menthol23 and other flavours that can mask the harshness of tobacco24 and may appeal to female and young non-smokers 21 25–28. Therefore, it is critical to monitor the growth, toxicity and potential public health impact of heat-sticks with and without flavour capsules, as well as the continuing growth of capsule cigarettes.…”
mentioning
confidence: 99%